OPTIMALISASI TEORI KOMUNIKASI UNTUK MENINGKATKAN PEMASARAN DIGITAL @maktabah_imamsyafii DI INSTAGRAM - Mikhral Rinaldi; Nabila Putri; Rizki Syahputra (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The rapid development of communication technology and social media has created significant opportunities for businesses to introduce and market products digitally. This article examines the digital marketing communication strategy implemented by @maktabah_imamsyafii, a publisher and distributor of religious books, which utilizes Instagram as a platform to enhance product recognition and sales. Before transitioning to digital marketing, Maktabah Imam Syafii relied on traditional marketing methods that had limitations in terms of reach and time. Since adopting Instagram in August 2016, they have successfully increased their follower count to 5,000 and experienced a 37% increase in sales. This study employs a qualitative case study approach to identify the factors influencing the success of their digital marketing strategy. The findings show that using Instagram as an interactive and persuasive communication channel has strengthened their relationship with the audience and enhanced customer loyalty. Informative content, attractive promotions such as giveaways and discounts, and a personalized approach in interacting with customers have proven effective in increasing engagement and sales. Despite facing challenges from rapid changes in digital consumption trends, the study emphasizes the importance of adaptive marketing strategies based on data analytics to maintain success in the digital age. The findings are expected to provide valuable insights for other businesses in optimizing digital marketing on social media.